Changes in Soil Chemical Properties and Growth of Palm Oil (Elaeis guineensis Jacq) with Comparative Composition of Plant Media - Murnita Murnita; Yulfi Desi; Meriati Meriati (Jurnal Penelitian Pendidikan IPA, 2024)
One of the benefits of Oil Palm Empty Fruit Bunches (OPEFB) waste can be processed into bokashi as a planting medium for oil palm nurseries. The research aims to: Determine changes in soil chemical properties due to the comparison of planting media, and obtain the best ratio of planting media to the best seedling growth in Main-Nursery. The research was conducted in Koto Panjang Ikur Koto Village, Koto Tangah District, Padang City. The study was conducted in January-April 2022. RAL design (completely randomized design) with 4 treatments and 6 replications. One experimental unit consist of 3 polybags of plants so there are 72 polybags of plants. Treatment: A = Control (Without Bokashi OPEFB), B = Topsoil: Bokashi OPEFB (1:3), C = Topsoil: Bokashi OPEFB (1:1), and D = Topsoil : Bokashi OPEFB (3:1). The results showed: Treatment B or Topsoil : Bokashi OPEFB (1:3) is the best, cause increase in soil chemical properties: pH 1.17 units; C-organic 1.98%; N-total 0.11%; P-available 4.01 ppm; K-dd 0.48 me/100g; Mg-dd 1.42 me/100g; and Ca-dd 2.67 me/100g. OPEFB bokashi application was significantly different to increase the plant height, not significant to wet weight and dry weight of the plant.